Analisis Pengaruh Produk Domestik Regional Bruto (PDRB) Terhadap Penyerapan Tenaga Kerja Di Provinsi Lampung - Habiburrahman HABIBURRAHMAN (Jurnal Manajemen dan Bisnis, 2012)
This research investigates the influence the Regional Gross Domestic Product to employment absorption. The problems in the Lampung Province are low employment absorption, and fluctuated Regional Gross Domestic Product growth . It is not yet known how the contribution Regional Gross Domestic Product to employment absorption The explanatory method is applied in this research which aims to clarify the causal relationship among the variables and to test the hypotheses. The research used time series secondary data of 30 years and was analysed by multivariate linear regression analysis with Ordinary Least Square (OLS) technique using Eviews program of version 7.0.The findings of this research show that the employment absorption also depends on Regional Gross Domestic Product. This research also reveals that the Regional Gross Domestic Product is a strategy to improve the employment absorption in Lampung Province.